Improving Learning Quality through Quizizz Paper Mode: A Quantitative Study of Elementary School Students - Pratiwi Saputri; Nazurty Nazurty; Urip Sulistiyo (Universitas Negeri Semarang, 2025)
Background - Low student motivation remains a persistent challenge in elementary education, particularly when conventional assessment methods fail to stimulate engagement. In schools with limited digital infrastructure, educators often struggle to integrate interactive learning tools that could foster active participation and improve academic outcomes. Purpose - This study aims to investigate the effect of Quizizz Paper Mode, a gamified non-digital assessment tool, on enhancing elementary students’ learning motivation. Method/approach - The study employed a quantitative approach using a One Group Pretest-Posttest Design involving 30 third-grade students at SD Negeri 28/IV Kota Jambi. The intervention spanned four learning sessions over two weeks, covering core subjects such as mathematics and science. Students’ motivation levels were measured using a validated Likert-scale questionnaire, supported by classroom observations and interviews. Statistical analysis included descriptive comparison and a paired t-test. Findings - The findings showed a significant improvement in students' learning motivation, with the average score increasing from 55.3 (moderate) to 78.6 (high). The paired t-test yielded a t-value of 7.89 and a p-value < 0.001, indicating statistical significance. Observations revealed enhanced student participation, confidence, and enthusiasm during the learning process. Conclusions - The implementation of Quizizz Paper Mode effectively increased students’ learning motivation, supported a more interactive classroom environment, and simplified the formative assessment process for teachers. Novelty/Originality/Value - This study contributes new empirical insights on the use of gamified paper-based assessments in contexts where digital access is limited. It highlights Quizizz Paper Mode as a viable and innovative alternative for fostering student motivation and engagement, particularly in under-resourced elementary school settings.